Comparison of rhombic type micromixer to improve mixing efficiency in biomems application. - Salleh, Mariam (2013)
The term lab on chip and micro total analysis system stand synonymous for devices that require handling and processing of small amount of fluid to perform function such as sample preparation, separation, biosensing and detection. Constraint to the long mixing channel and miniaturized in size but efficiently mixed between fluids. In this project, the three types of rhombic geometry design were studied to characterize mixing performance between the blood sample and reagents. Pure rhombic, branch rhombic and slanted groove rhombic glass based micromixer were proposed to study the mixing performance. The simulation was obtained using CoventorWare 2010. The laminar mixing between blood sample and reagent was simulated at low Reynolds number flow (Re <<1). Reagents used are toluene-low viscosity reagent and carbolic acid- higher viscosity reagent in comparison to blood. mixing characterization will be optimized based on visualization result of the distribution field in term of viscosity. Image standard deviation (σ) is used to characterize fluid mixing; the lower σ, the better in fluids mixing properties. From study, it was found that slanted groove rhombic gained the highest mixing efficiency followed by pure rhombic and branch rhombic. This is because grooves structure can improve surface contact area thus stretch and folds the laminar flows.